MR-guided Cryoablation for the Treatment of Symptomatic Pedal Vascular Malformations. Issue 4 (3rd December 2021) - Knavel Koepsel, Erica M.; Thompson, Scott; Bendel, Emily C.; Augustine, Matthew; Tollefson, Megha M.; Gorny, Krzysztof R.; Lu, Aiming; Favazza, Christopher P.; Woodrum, David A.
Abstract : Objective: Vascular malformations are benign vascular anomalies characterized by abnormally developed arterial, venous, and lymphatic structures, which are often symptomatic. Historical and current treatment techniques include intravascular embolization/sclerosis and surgical resection. While these techniques have proven to be successful at managing and treating these types of lesions, these techniques are not without risk, especially in the small spaces of the hands and feet. Cryoablation for the treatment of low-flow vascular malformations is a new and evolving technique. We present five cases of symptomatic pedal vascular malformations treated with MR guided cryoablation, which provides encouraging safety and feasibility results for these difficult to treat lesions. Methods: A retrospective review of patients who had undergone MR-guided cryoablation of their pedal vascular malformations between January 2016 and January 2020 was performed. Results: Five cryoablations were completed without immediate complication. All patients reported markedly decreased pain corresponding to the treated area and improvement in their ability to return to a more active lifestyle. Two patients experienced mild transient numbness which resolved by 2–3 months and one patient experienced a transient motor and sensory neuropathy which resolved by 6 months. Conclusion: We present five cases of successful MR-guided cryoablation of symptomatic pedal venous malformations. Many of the patients included in this review failed conservative and other interventional/surgical treatments. The treatment options for this patient cohort can be limited given small space within the plantar aspect of the foot. Cryoablation of these lesions can be performed safely especially under continuous MRI monitoring. Level of Evidence: Case series (Level 4)